Evaluation of the role of MSCT airway mapping in guiding trans-bronchial lung biopsy in cases of inaccessible lung lesions - Youssriah Yahia Sabri; Khaled Mahmoud Kamel; Mona Ahmed Fouad Hafez; Sara Mohamed Saleh Saleh Nasef (The Egyptian Journal of Radiology and Nuclear Medicine, 2017)
Objective: This work aimed for using multislice computed tomography (MSCT) to map the bronchial tree and assess the exact site, direction, airway findings and bronchial measurements to guide trans-bronchial lung biopsy from an inaccessible lung lesion. Patients and methods: This study was carried on 26 patients. It was conducted in the Radiology Department, in collaboration with Chest Department, in the period from January 2015 to April 2016. All patients were subjected to Virtual Bronchographic (VB) examination and Trans-Bronchial lung biopsy (in selected cases guided by the VB results). Results: In this study, MSCT-VB maps guided the fiber-optic bronchoscopy in 30 bronchial lesions in 26 patients to the proper sampling site for different lung lesions with success rate 100% and CT maps were done, reaching 3rd to 7th order bronchial generation with mean distance from central bronchi was 21.3 mm and mean target bronchial diameter was 1.9 mm. Right sided lesions encountered in 57.7% and left sided lesions in 42.3% with the most common segmental affection was the right upper lobe in 36.7% of bronchial lesions and the apico-posterior subsegment of left upper lobe in 23.3% of lesions, then planning according to the site of the lesion in relation to the bronchial tree in the VB was done. Histopathological assessment was done with 61.5% neoplastic lesions and 38.5% inflammatory lesions. Conclusion: Multiplanar reconstruction images together with virtual bronchographic images were accurate in the detection of lesion’s site, depiction of degree of narrowing, and distal visualization of airways. This CT map should be used to guide bronchoscopy or to direct trans-bronchial needle biopsy to guarantee positive histopathological results.